Pelatihan Penyusunan Business Model Canvas (BMC) Sebagai Strategi Pengembangan UMKM di Desa Bojong Baru, Kecamatan Bojonggede, Kabupaten Bogor - Rachmah, Siti Mabrur; Siska, Elmira; Lestari, Nurlaela Eva Puji; Elvira, Lela (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2025)
This Community Service (PKM) activity aims to improve the understanding and skills of MSME actors in Bojong Baru Village in designing structured business strategies through the Business Model Canvas (BMC) approach. The implementation method consists of three stages, namely preparation, implementation and evaluation of activities. The preparation stage includes coordination with partners to identify problems and prepare training materials. The implementation stage includes delivering materials, direct practice in preparing the BMC matrix, and discussion and question and answer sessions. This stage involved 4 lecturers, 3 students, and 25 members of the MSME forum who were all present and showed high enthusiasm throughout the activity. The evaluation stage was carried out by analyzing the results of the questionnaire to measure the participants' understanding and satisfaction with the activity. The evaluation results showed that the material presented was in accordance with the needs of the partners. Most participants felt that they had gained new insights and improved skills in developing more focused and adaptive business strategies. In conclusion, this PKM activity has succeeded in providing a positive impact on strengthening the capacity of MSMEs through an educational approach that is applicable and participatory, and has the potential to encourage the growth of MSMEs that are more competitive and sustainable. This activity is expected to be an initial step in encouraging the Bojong Baru Village MSME Forum to be more ready to compete through more focused, creative, and adaptive business strategies to market changes.